A rare case of pleural effusion due to Prevotella dentalis. (December 2018) - Cobo, Fernando; Calatrava, Elizabeth; Rodríguez-Granger, Javier; Sampedro, Antonio; Aliaga-Martínez, Luis; Navarro-Marí, José María
Abstract: Prevotella dentalis is a Gram-negative anaerobic rod involved in various human diseases, especially oral infections. We report a rare case of a pleural effusion due to this microorganism in an elderly patient. An 88-year-old man with chronic respiratory disease presented with a left pleural effusion for more than 1 month. Culture of drained pleural fluid resulted in isolation of P. dentalis . Resistance to penicillin and moxifloxacin was documented. Treatment with drainage and clindamycin was established, but the patient developed cognitive impairment and died after a worsening of his general condition. Highlights: Prevotella species are often associated with odontogenic infections. P. dentalis is a common cause of human infection, especially periodontitis. Mass spectrometry may be highly useful in the diagnosis of anaerobes. P. dentalis is a very rare cause of pleural effusion.